Direct identification of residues of the epidermal growth factor receptor in close proximity to the amino terminus of bound epidermal growth factor. - Woltjer, R L (1992)
We have recently developed a kinetically controlled, step-wise affinity cross-linking technique for specific, high-yield, covalent linkage of murine epidermal growth factor (mEGF) via its N terminus to the EGF receptor. EGF receptor from A431 cells was cross-linked to radiolabeled mEGF (125I-mEGF) by this technique and the 125I-mEGF-receptor complex was purified and denatured. Tryptic digestion of this preparation gave rise to a unique radiolabeled peptide that did not comigrate with trypsin-treated 125I-mEGF in SDS/Tricine gels but that could be immunoprecipitated with antibodies to mEGF. The immunoprecipitated peptide was isolated by electrophoresis in SDS/Tricine gels, eluted, and sequenced. The sequence was found to correspond to that of a tryptic peptide of the EGF receptor beginning with Gly-85, which is in domain I, a region N terminal to the first cysteine-rich region of the receptor. Selective loss of signal in the 17th sequencing cycle suggests that the point of attachment of N-terminally modified 125I-mEGF to the receptor is Tyr-101. The data presented here provide identification by direct protein microsequencing of a site of interaction of EGF and the EGF receptor.